Analisis Pembiayaan Yayasan Pendidikan IslamAl Adli Melalui Corporate Social Responsibility PT. Sentosa Mulia Bahagia - Yuliasandy, Yuliasandy; Sugara, Kathryn (Jurnal Akuntansi dan Keuangan, 2025)
This qualitative research aim to analyse the financial expenditure of Al Adli Islamic Education Foundation which also part of the CSR activity program of a private limited company Sentosa Mulia Bahagia Ltd. Al Adli Foundation that is based in Palembang has been fully financially supported by Sentosa Mulia Bahagia Ltd. In terms of infrastructure building and maintenance expenditure, operational cost, scholarships for outstanding student and underprivileged student, also human resource training and staff skill development. This research shows that every expense can be established by going through a standard procedure which includes analysing the foundation needs, carrying out a survey, identifying priority needs, undertake financial planning and monitoring, and finally evaluation until the payment process completed. The main purpose of the private limited company is to be socially responsible to the social environment by increasing the education quality, social development, opening opportunities for low cost accredited education, and building good relationship with the society and other stakeholders.